Lepage-type change-pointcontrol chartsapplied to monitoring acute mal-nutrition in under-5 children in Nigeria (2017)
Introduction: Identification of the most affected age is an important statistical contribution to monitoring nutritional problems among children. Previous studies have demonstrated that monitoring processes’ parameters (mean and variability) individually or simultaneously could provide some insights but no application has been related to monitoring proportion of wasting in under-5 children. The present study applied a nonparametric-based Lepage-type change-point (LCP) control chart to monitor the proportion of acute malnutrition in under-5 children in Nigeria. Methods: Data were extracted for 24,530 under-5 children with valid and complete information on date of birth, height and weight in the 2013 Nigeria Demographic and Health Survey dataset. Data were analysed using descriptive statistics including mean, standard deviation and proportion. The Shapiro-Wilk lamda was used to assess the normality of the distribution of wasting among under-5 while the LCP control chart was used for monitoring the distribution. Affter-signal diagnosis was conducted to ascertain what distributional data parameters have changed, at 5% level of significance. Results: Children were 23.8(±16.8) months old and mostly female (50.3%). Prevalence of wasting among under-5 was 18.4% and higher among children aged 0-55 months (24.9%). Normality test (Shapiro-Wilk: W= 0.9268; p=0.001463) suggested that the distribution of wasted children was non-normal. The LCP chart signalled a shift (abnormal rate) in the proportion of wasting at aged 24 month; while its estimated change-point was at age 21 month. After-signal diagnosis indicated the change may have occurred in both a location shift (p=0.002949) and a variability shift (p=0.03978) of the proportion of wasted children. Conclusion: Prevalence of wasting in the present analysis is not uniform across age groups and the LCP chart demonstrated prompt detection of shift (both in mean and variability) in the proportion of wasted under-5 children. The LCP chart could be used to monitor proportion of wasting among children to identify groups needing intervention